Corrosion of Conductor Rolls in an Electrogalvanizing Line - Egli, Walter Alfredo (2012)
Conductor rolls in continuous cold rolled steel strip horizontal acid electrogalvanizing lines after some period of service suffer a surface deterioration that alters its color, aspect and eventually its roughness what is more deleterious to its good performance. The surface degradation finally produce a pattern on the roll surface that is transferred or copied to the electrogalvanized strip surface originating quality defects that could make some level of rejections in high quality products. This process has been historically thought as an erosion-corrosion one. This work shows some interesting results that help in the understanding of the nature of this specific corrosion mechanism. It is also presented a new method capable of evaluate the corrosion resistance of new materials for construction of conductor rolls for this type of industrial process. Finally a comparison of the corrosion resistance of different alloys using this technique was made.